2016
DOI: 10.1016/j.tube.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes and differentially expressed efflux pump genes in Mycobacterium tuberculosis exposed to a rifampicin and verapamil combination

Abstract: The aim of the present study was to (i) evaluate the in vitro action of rifampicin (RIF), ethambutol or isoniazid with efflux pumps inhibitors (EPIs) in Mycobacterium tuberculosis (Mtb) H37Rv and (ii) evaluate the morphological and efflux pumps (EPs) transcriptional changes by the action of rifampicin + verapamil combination (RIF + VP). The minimal inhibitory concentration and synergic effect of drug combinations were determined by Resazurin Microtiter Plate Assay and Resazurin Drugs Combination Microtiter Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 26 publications
(55 reference statements)
3
35
0
Order By: Relevance
“…Ethidium bromide (EtBr) is considered a broad substrate of efflux pumps, most of which require the PMF ( 33 , 34 ), and has been used as a probe to monitor the activity of efflux pumps in mycobacteria ( 35 ). Verapamil has been shown to affect the intracellular accumulation of EtBr in M. tuberculosis ( 36 , 37 ), an effect generally attributed to direct inhibition of efflux pumps. However, dissipation of the PMF by verapamil could impair efflux, in turn leading to increased intracellular EtBr concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethidium bromide (EtBr) is considered a broad substrate of efflux pumps, most of which require the PMF ( 33 , 34 ), and has been used as a probe to monitor the activity of efflux pumps in mycobacteria ( 35 ). Verapamil has been shown to affect the intracellular accumulation of EtBr in M. tuberculosis ( 36 , 37 ), an effect generally attributed to direct inhibition of efflux pumps. However, dissipation of the PMF by verapamil could impair efflux, in turn leading to increased intracellular EtBr concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Verapamil has been shown to increase the intracellular accumulation of EtBr, a broad substrate of mammalian efflux pumps ( 33 , 34 ) commonly used as a probe of efflux pump activity in bacteria ( 35 ), in M. tuberculosis ( 36 ). We have reproduced those results and found EtBr and verapamil to be synergistic.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have demonstrated the importance of the overexpression of efflux pump genes in MDR and XDR M . tuberculosis clinical strains (Calgin et al, 2013; Coelho et al, 2015; Li et al, 2015a; Yamchi et al, 2015; Kanji et al, 2016; Machado et al, 2016; Oh et al, 2017), in rifampicin monoresistant strains (Li et al, 2015b), or in the H37Rv susceptible strain after exposure to drugs (Garima et al, 2015; Caleffi-Ferracioli et al, 2016). Nevertheless, most of these studies are based on the simple assessment and evaluation of the levels of expression of M. tuberculosis efflux pump genes, and few have determined the effect of efflux inhibitors on the MICs of the antituberculosis drugs and have quantified the activity of the overexpressed efflux systems.…”
Section: Discussionmentioning
confidence: 99%
“…Along with cell wall permeability, active efflux systems also provide resistance by expelling the drug molecules that enter the cell. Several mycobacterial drug efflux pumps have been identified and can be grouped into five different structural families: the major facilitator superfamily (MFS) (Siddiqi et al, 2004; Balganesh et al, 2012; Xu et al, 2015), the small multidrug resistance (SMR) family (De Rossi et al, 2002; Garima et al, 2015), the resistance-nodulation-cell division (RND) superfamily (De Rossi et al, 2006; Murakami et al, 2006), the adenosine triphosphate (ATP)-binding cassette (ABC) superfamily (Bhatt et al, 2000; Choudhuri et al, 2002; Pasca et al, 2004; Lubelski et al, 2007; Caleffi-Ferracioli et al, 2016) and the multidrug and toxic compound extrusion (MATE) family (Table 2) (Mishra and Daniels, 2013). …”
Section: Drug Resistance Mechanisms In Mycobacteriamentioning
confidence: 99%